A SUPERFLUOUS WRONG NAME FOR THE "LANGSAT" (LANSIUM AQAEUM MIQ.) - A.J.G.H. KOSTERMANS (Reinwardtia, 1988)
In the Indian Forester 100(2): 202. Mar. 1974, K.A. Salm and S.R.R. Bennet published an automatic transfer (without having seen the type material) of Melia parasitica Osbeck (Dagbock Ostind. Resa 278. 1751; ed. german. 1765; ed. angl. 1771) to Lansium parasiticum (Osb.) Salm & Bennet, apparently influenced by Merril's suggestion (in J. Arnold Arb. 3:528. 1916 and 33: 229. 1952), who referred it to Lansium domesticum.